The Spirit as Gift in Acts : The Spirit's Empowerment of the Early Jesus Community - Griffiths, John D. (Journal of Pentecostal Theology Supplement Series, 2022)
"What does Luke mean when he describes the Spirit as gift (Acts 2:38)? This study explores the social implications of gift-giving in the Greco-Roman world, arguing that gifts initiate and sustain relationships. Therefore, the description of the Spirit as gift is inherently social, which is shown in the Spirit's empowerment of the teaching, unity, meals, sharing of possessions and worship of the early Jesus community. The Spirit as gift then leads us to see that the early Jesus community is 'the community of the Holy Spirit'"--